NUMERICAL ANALYSIS OF ELECTRIC FORCE DISTRIBUTION ON TUMOR MASS IN DC ELECTRIC FIELD EXPOSURE - Muhammad Arif; Warsito Purwo Taruno; Septelia Inawati Wanandi; Anto Sulaksono (Program Studi Fisika Universitas Negeri Jakarta, 2021)
Researchers have used electric fields as a new therapeutic strategy to treat cancer for the past 15 years. Tumor Treating Fields (TTFields) is an alternating electric field-based cancer therapy approved by the US FDA to treat glioblastoma multiforme (GBM). ECCT (Electro-Capacitive Cancer therapy), a DC charged-discharged electric field (EF) cancer therapy, also shows a performance inhibiting cell proliferation. ECCT affects the cancer lesions to cause simultaneous death of the cancer cell and detached off of the surrounding tissue. The author hypothesizes that the EF produces an electric force that is not homogeneous throughout the tumor mass and generates a strong dielectrophoresis force. The force affects microtubules polymerization during mitosis and causes mitotic arrest. To examine this hypothesis, we performed a numerical simulation of the EF distribution and calculated the force acting on the tumor mass generated by the EF. We analyzed DC electric field exposure on a cancer lesion using a single lesion 2D circular model, calculated the EF intensity on the lesion using the Finite Element Method, and the dielectrophoresis force distribution to quantify the treatment efficacy. The results showed that the distribution of EF intensity was not homogeneous at the lesion-medium boundary and homogeneous within the lesion. The EF intensity is highly dependent on the dielectric constant of the medium and the applied voltage difference that may affect the effectiveness of the treatment. Variations in lesion diameter had no significant effect on the EF intensity distribution and, hence the effectiveness of the therapy. It is considered that EF exposure by ECCT generated strong force on the lesion-medium boundary that could cause detachment of the tumor mass from the surrounding tissue.